Realistic, modern and postmodern dominants in the modern world - Aygul Onalbaeba, Kuralay Zhanuzakova; Yerkinbek Turgunov, Zhanakul Sametova (Opción, 2019)
This article discusses the realistic, modern and postmodern dominants in the modern world and in the Kazakh literature via the use of autobiographism as an important method in plot development. As a result, the assessment of religious-philosophical symbols is a sign of the process of scientific decolonization in the humanities. In conclusion, there is a strong spiritual foundation, which is based on the events of the history of Islam or the life of historians, who founded the religion of Islam, as a basis for our spirituality in the works written by Kazakh prose writers.